Experimental perfect state transfer of an entangled photonic qubit - Chapman, Robert J.; Santandrea, Matteo; Huang, Zixin; Corrielli, Giacomo; Crespi, Andrea; Yung, Man-Hong; Osellame, Roberto; Peruzzo, Alberto (Nature Communications)

Systematik zur innovationsorientierten Kompetenzplanung - Rübbelke, René

Systematik zur technologie-induzierten Produkt- und Technologieplanung - Wall, Marina

Selfish Network Creation - On Variants of Network Creation Games - Cord-Landwehr, Andreas

Instrumentarium für einen lösungsmusterbasierten Entwurf fortgeschrittener mechatronischer Systeme - Anacker, Harald

Methodik zur Bewertung von Produktionssystemen in der frühen Entwicklungsphase - Rudtsch, Vinzent

Systematik zur lösungsmusterbasierten Entwicklung von Frugal Innovations - Lehner, Anne-Christin

Systematik zur musterbasierten Entwicklung technologie-induzierter Geschäftsmodelle - Amshoff, Benjamin

Multipartite Entanglement of a Two-Separable State - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Quantum Correlations from the Conditional Statistics of Incomplete Data - Sperling, Jan; Bartley, Tim; Donati, G.; Barbieri, M.; Jin, X.-M.; Datta, A.; Vogel, W.; Walmsley, I. A. (Physical Review Letters)

Gaussian entanglement in the turbulent atmosphere - Bohmann, M.; Semenov, A. A.; Sperling, Jan; Vogel, W. (Physical Review A)

Operational definition of quantum correlations of light - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review A)

Characterizing maximally singular phase-space distributions - Sperling, Jan (Physical Review A)

Multitime correlation functions in nonclassical stochastic processes - Krumm, F.; Sperling, Jan; Vogel, W. (Physical Review A)

Witnessing random unitary and projective quantum channels: Complementarity between separable and maximally entangled states - Bruns, D.; Sperling, Jan; Scheel, S. (Physical Review A)

Harnessing click detectors for the genuine characterization of light states - Heilmann, René; Sperling, Jan; Perez-Leija, Armando; Gräfe, Markus; Heinrich, Matthias; Nolte, Stefan; Vogel, Werner; Szameit, Alexander (Scientific Reports)

Health Shocks and Risk Aversion - Schmitz, Hendrik; Decker, S. (Journal of Health Economics 50, 154-170)

Design of virtual research environments for {\ "u} r detailed philological work - Keil, Reinhard ("Eh, the old man, I would like to pay attention". Festschrift for {\ "u} r Joachim Veit for his 60th birthday)

Decentralized provenance-aware publishing with nanopublications - Kuhn, Tobias; Chichester, Christine; Krauthammer, Michael; Queralt-Rosinach, Núria; Verborgh, Ruben; Giannakopoulos, George; Ngonga Ngomo, Axel-Cyrille; Viglianti, Raffaele; Dumontier, Michel (PeerJ Comput. Sci.)

A fine-grained evaluation of SPARQL endpoint federation systems - Saleem, Muhammad; Khan, Yasar; Hasnain, Ali; Ermilov, Ivan; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

An Efficient Approach for the Generation of Allen Relations - Georgala, Kleanthi; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (ECAI 2016 - 22nd European Conference on Artificial Intelligence, 29 August-2 September 2016, The Hague, The Netherlands - Including Prestigious Applications of Artificial Intelligence {(PAIS} 2016))

Towards SPARQL-Based Induction for Large-Scale RDF Data Sets - Bin, Simon; Bühmann, Lorenz; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (ECAI 2016 - 22nd European Conference on Artificial Intelligence, 29 August-2 September 2016, The Hague, The Netherlands - Including Prestigious Applications of Artificial Intelligence {(PAIS} 2016))

TAIPAN: Automatic Property Mapping for Tabular Data - Ermilov, Ivan; Ngonga Ngomo, Axel-Cyrille (Knowledge Engineering and Knowledge Management - 20th International Conference, EKAW 2016, Bologna, Italy, November 19-23, 2016, Proceedings)

DBtrends: Publishing and Benchmarking RDF Ranking Functions - Marx, Edgard; Zaveri, Amrapali; Mohammed, Mofeed; Rautenberg, Sandro; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille; Cheng, Gong (Proceedings of the 2nd International Workshop on Summarizing and Presenting Entities and Ontologies (SumPre 2016) co-located with the 13th Extended Semantic Web Conference {(ESWC} 2016), Anissaras, Greece, May 30, 2016)

6th Open Challenge on Question Answering over Linked Data (QALD-6) - Unger, Christina; Ngonga Ngomo, Axel-Cyrille; Cabrio, Elena (Semantic Web Challenges - Third SemWebEval Challenge at ESWC 2016, Heraklion, Crete, Greece, May 29 - June 2, 2016, Revised Selected Papers)

The Lazy Traveling Salesman - Memory Management for Large-Scale Link Discovery - Ngonga Ngomo, Axel-Cyrille; M. Hassan, Mofeed (The Semantic Web. Latest Advances and New Domains - 13th International Conference, ESWC 2016, Heraklion, Crete, Greece, May 29 - June 2, 2016, Proceedings)

Federated Query Processing: Challenges and Opportunities - Ngonga Ngomo, Axel-Cyrille; Saleem, Muhammad (Proceedings of the 3rd International Workshop on Dataset PROFIling and fEderated Search for Linked Data {(PROFILES} '16) co-located with the 13th ESWC 2016 Conference, Anissaras, Greece, May 30, 2016)

UPSP: Unique Predicate-based Source Selection for SPARQL Endpoint Federation - Cem Ozkan, Ethem; Saleem, Muhammad; Dogdu, Erdogan; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 3rd International Workshop on Dataset PROFIling and fEderated Search for Linked Data {(PROFILES} '16) co-located with the 13th ESWC 2016 Conference, Anissaras, Greece, May 30, 2016)

Detecting Similar Linked Datasets Using Topic Modelling - Röder, Michael; Ngonga Ngomo, Axel-Cyrille; Ermilov, Ivan; Both, Andreas (The Semantic Web. Latest Advances and New Domains - 13th International Conference, ESWC 2016, Heraklion, Crete, Greece, May 29 - June 2, 2016, Proceedings)

Big data architecture for the semantic analysis of complex events in manufacturing - F. Huber, Marco; Voigt, Martin; Ngonga Ngomo, Axel-Cyrille (46. Jahrestagung der Gesellschaft für Informatik, Informatik von Menschen für Menschen, INFORMATIK 2016, Klagenfurt, Austria, September 26-30, 2016)

Requirements to Modern Semantic Search Engine - Usbeck, Ricardo; Röder, Michael; Haase, Peter; Kozlov, Artem; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (Knowledge Engineering and Semantic Web - 7th International Conference, KESW 2016, Prague, Czech Republic, September 21-23, 2016, Proceedings)

Exploring Term Networks for Semantic Search over RDF Knowledge Graphs - Marx, Edgard; Höffner, Konrad; Shekarpour, Saeedeh; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens; Auer, Sören (Metadata and Semantics Research - 10th International Conference, MTSR 2016, Göttingen, Germany, November 22-25, 2016, Proceedings)

Instance matching benchmark for spatial data: a challenge proposal to OAEI - Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th International Workshop on Ontology Matching co-located with the 15th International Semantic Web Conference {(ISWC} 2016), Kobe, Japan, October 18, 2016)

How Well Does Your Instance Matching System Perform? Experimental Evaluation with LANCE - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Workshop on Benchmarking Linked Data {(BLINK} 2016) co-located with the 15th International Semantic Web Conference (ISWC), Kobe, Japan, October 18, 2016)

Lion's Den: feeding the LinkLion - Ahmed Sherif, Mohamed; M. Hassan, Mofeed; Soru, Tommaso; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (Proceedings of the 11th International Workshop on Ontology Matching co-located with the 15th International Semantic Web Conference {(ISWC} 2016), Kobe, Japan, October 18, 2016)

Big Data Acquisition - Lyko, Klaus; Nitzschke, Marcus; Ngonga Ngomo, Axel-Cyrille (New Horizons for a Data-Driven Economy - A Roadmap for Usage and Exploitation of Big Data in Europe)

Knowledge Engineering and Semantic Web - 7th International Conference, KESW 2016, Prague, Czech Republic, September 21-23, 2016, Proceedings

Proceedings of the Workshop on Benchmarking Linked Data (BLINK 2016) co-located with the 15th International Semantic Web Conference (ISWC), Kobe, Japan, October 18, 2016

LITMUS: An Open Extensible Framework for Benchmarking RDF Data Management Solutions - Thakkar, Harsh; Dubey, Mohnish; Sejdiu, Gezim; Ngonga Ngomo, Axel-Cyrille; Debattista, Jeremy; Lange, Christoph; Lehmann, Jens; Auer, Sören; Vidal, Maria-Esther (CoRR)

Self-Wiring Question Answering Systems - Usbeck, Ricardo; Huthmann, Jonathan; Duldhardt, Nico; Ngonga Ngomo, Axel-Cyrille (CoRR)

Annex: Radon - Rapid Discovery of Topological Relations - Ahmed Sherif, Mohamed; Dreßler, Kevin; Smeros, Panayiotis; Ngonga Ngomo, Axel-Cyrille (CoRR)

An Evaluation of Models for Runtime Approximation in Link Discovery - Georgala, Kleanthi; Hoffmann, Michael; Ngonga Ngomo, Axel-Cyrille (CoRR)

HOBBIT: Holistic Benchmarking of Big Linked Data - Ngonga Ngomo, Axel-Cyrille; García-Rojas, Alejandra; Fundulaki, Irini (ERCIM News)

Decentralized provenance-aware publishing with nanopublications - Kuhn, Tobias; Chichester, Christine; Krauthammer, Michael; Queralt-Rosinach, Núria; Verborgh, Ruben; Giannakopoulos, George; Ngonga Ngomo, Axel-Cyrille; Viglianti, Raffaele; Dumontier, Michel (PeerJ Prepr.)

Driven discrete time quantum walks - Hamilton, Craig S; Barkhofen, Sonja; Sansoni, Linda; Jex, Igor; Silberhorn, Christine (New Journal of Physics)

Quantum walks with dynamical control: graph engineering, initial state preparation and state transfer - Nitsche, Thomas; Elster, Fabian; Novotný, Jaroslav; Gábris, Aurél; Jex, Igor; Barkhofen, Sonja; Silberhorn, Christine (New Journal of Physics)

Vorstellungen von Studentinnen und Studenten des Lehramts an Grundschulen in Bezug auf die Gestaltung des individualisierten, inklusiven Unterrichts - Hellmich, Frank; Görel, Gamze; Ort, Margarita (Individualisierung im Grundschulunterricht: Anspruch, Realisierung und Risiken)

Erfahrungen und Selbstwirksamkeitsüberzeugungen in Bezug auf inklusiven Unterricht bei Grundschullehrkräften - Hellmich, Frank; Görel, Gamze (Facetten grundschulpädagogischer und -didaktischer Forschung)

Einstellungen und Motivation von Lehramtsstudentinnen und -studenten in Bezug auf den inklusiven Unterricht in der Grundschule. Ein Vergleich zwischen Deutschland und Österreich - Hellmich, Frank; Görel, Gamze; Schwab, Susanne (Empirische Sonderpädagogik)
In Folge der Ratifizierung der UN-Konvention über die Rechte von Menschen mit Behinderungen durch die deutschsprachigen Länder ergeben sich an verschiedenen Stellen in den Bildungssystemen Herausforderungen, die es zukünftig mit dem Blick auf die Gestaltung inklusiver Bildungsprozesse erfolgreich zu bewältigen gilt. Im Besonderen stellt sich gegenwärtig die Frage nach effizienten Möglichkeiten der Ausbildung angehender Lehrerinnen und Lehrer für inklusive Schulen. In unserer Studie untersuchen wir einerseits Unterschiede in Einstellungen zur Inklusion, Selbstwirksamkeitsüberzeugungen, Motivation sowie Erfahrungen aus dem integrativen bzw. inklusiven Unterricht im Rahmen von Schulpraktika zwischen Lehramtsstudentinnen und -studenten mit dem Studienschwerpunkt Grundschule aus Deutschland (N=765) und Österreich (N=519). Die Ergebnisse geben Hinweise darauf, dass die österreichischen Studentinnen und Studenten über signifikant positivere Einstellungen zur Inklusion sowie über signifikant höhere Selbstwirksamkeitsüberzeugungen in Bezug auf die zukünftige Gestaltung inklusiven Unterrichts verfügen als die deutschen Studentinnen und Studenten. Darüber hinaus wird anhand von Strukturgleichungsmodellen deutlich, dass sich Einstellungen zur Inklusion in beiden Stichproben über die Selbstwirksamkeitsüberzeugungen sowie über die Erfahrungen mit inklusivem Unterricht aus Schulpraktika bei den Studentinnen und Studenten erklären lassen. Die Motivation, sich im Studium mit inklusionspädagogischen Fragestellungen zu beschäftigen, wird in beiden Stichproben über die Einstellungen zur Inklusion vorhergesagt. (DIPF/Orig.)

Kognitiv-mathematische Förderung - Hellmich, Frank (Arbeitsfelder der Kindheitspädagogik. Eine Einführung)

Lehren und Lernen im Geometrieunterricht - Hellmich, Frank (Didaktik des Unterrichts im Förderschwerpunkt Lernen. Ein Handbuch für Studium und Praxis)

Reanalyzing Zero Returns to Education in Germany - Kamhöfer, Daniel A.; Schmitz, Hendrik (Journal of Applied Econometrics)

Lesestrategien und Wortschatzarbeit zur Förderung der Lesekompetenzen von mehrsprachig aufwachsenden Kindern in der Grundschule - Hellmich, Frank; Niebuhr-Siebert, Sandra (Leseförderung mit (mehrsprachigen) Kindern in Grundschulen. Wortschatz, Lesetempo und Leseflüssigkeit fördern)

Gleichstellung und innerfamiliale Arbeitsteilung. Mahlzeitenmuster und Beköstigungsarbeit in Familien im Zeitvergleich - Klünder, Nina; Meier-Gräwe, Uta (Wie die Zeit vergeht. Analysen zur Zeitverwendung in Deutschland. Beiträge zur Ergebniskonferenz der Zeitverwendungserhebung)

Ermüdungsverhalten und mikrostrukturelle Charakterisierung der im Laserschmelzverfahren hergestellten Nickelbasis-Superlegierung Inconel 939 - Kanagarajah, Pirabagini
In der vorliegenden Arbeit wurden die mikrostrukturellen Eigenschaften und das dadurch resultierende mechanische Verhalten der im SLM-Verfahren (Selective Laser Melting) hergestellten Nickelbasis-Superlegierung Inconel 939 untersucht und einer Inconel 939 Gusslegierung gegenübergestellt. Die monotonen und mikrostrukturellen Untersuchungsergebnisse zeigen eine eindeutige Abhängigkeit der Herstellungsrichtung und deutliche Unterschiede zur Gusslegierung, insbesondere in der Mikrostruktur. Dehnungsgeregelte isotherme und thermomechanische Ermüdungsversuche in Kombination mit der Methode der digitalen Bildkorrelation (DIC) beschreiben das mechanische Verhalten sowie die kritischen Bereiche im Gefüge. Ob beim SLM- oder Gusswerkstoff eine höhere Lebensdauer bei der isothermen Ermüdung erreicht wird, ist von der Höhe der Beanspruchung abhängig. Im ausscheidungsgehärteten Zustand besitzt das SLM-Material bei niedrigen Belastungen und Temperaturen von Raumtemperatur bis 750 °C eine höhere Lebensdauer und zeigt somit ein besseres Ermüdungsverhalten als der Gusswerkstoff. Bei höheren Dehnungsamplituden werden vorhandene Poren aktiviert und ein schnelles Versagen tritt ein. Mit geeigneten HIP-Parametern konnte die Porosität allerdings deutlich reduziert werden.
Keywords: Nickelbasis-Superlegierung; Inconel 939; Laserschmelzverfahren; SLM; Ermüdung; Mikrostruktur

Glycaemic and insulin index of four common German breads - Goletzke, J; Atkinson, F S; Ek, K L; Bell, K; Brand-Miller, J C; Buyken, Anette (European Journal of Clinical Nutrition)

Commercial complementary food consumption is prospectively associated with added sugar intake in childhood - Foterek, Kristina; Buyken, Anette; Bolzenius, Katja; Hilbig, Annett; Nöthlings, Ute; Alexy, Ute (British Journal of Nutrition)
Abstract Given that commercial complementary food (CF) can contain high levels of added sugar, a high consumption may predispose to a preference for sweet taste later in life. This study examined cross-sectional associations between commercial CF consumption and added sugar intake in infancy as well as its prospective relation to added sugar intake in pre-school and primary-school age children. In all, 288 children of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study with 3-d weighed dietary records at 0·5 and 0·75 (infancy), 3 and 4 (pre-school age) and 6 and 7 years of age (primary-school age) were included in this analysis. Individual commercial CF consumption as percentage of total commercial CF (%cCF) was averaged at 0·5 and 0·75 years. Individual total added sugar intake (g/d, energy percentage/d) was averaged for all three age groups. Multivariable logistic and linear regression models were used to analyse associations between %cCF and added sugar intake. In infancy, a higher %cCF was associated with odds for high added sugar intake from CF and for high total added sugar intake (>75th percentile, P <0·033). Prospectively, a higher %cCF was related to higher added sugar intake in both pre-school ( P <0·041) and primary-school age children ( P <0·039), although these associations were attenuated in models adjusting for added sugar intake in infancy. A higher %cCF in infancy may predispose to higher added sugar intake in later childhood by virtue of its added sugar content. Therefore, offering home-made CF or carefully chosen commercial CF without added sugar might be one strategy to reduce sugar intake in infancy and later on.

Age and time trends in eating frequency and duration of nightly fasting of German children and adolescents - Roßbach, Sarah; Diederichs, Tanja; Bolzenius, Katja; Herder, Christian; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)

Prospective associations of meat consumption during childhood with measures of body composition during adolescence: results from the GINIplus and LISAplus birth cohorts. - Harris, C; Buyken, Anette; von Berg, A; Berdel, D; Lehmann, I; Hoffmann, B; Koletzko, S; Koletzko, B; Heinrich, J; Standl, M (Nutr J)

Residential Energy Storage from Repurposed Electric Vehicle Batteries — Market Overview and Development of a Service-Centered Business Model - Bräuer, sebastian; Monhof, Markus; Klör, Benjamin; Beverungen, Daniel (Proceedings of the IEEE Conference on Business Informatics (CBI 2016))

Modeling and simulation of metallic, particle-damped spheres for lightweight materials - Steinle, Tobias
Lightweight materials play an ever growing role in today's world. Saving on the mass of a machine will usually translate into a lower energy consumption. However, lightweight applications are prone to develop performance problems due to vibration induced by the operation of the machine. The Fraunhofer Institute for Manufacturing Technology and Advanced Materials in Dresden conducts research into the damping properties of composite materials. They are experimenting with hollow, particle filled spheres embedded in the lightweight material. Such a system is the technical motivation of this thesis. Ultimately, a numerical experiment to derive the coefficient of restitution is required. The simulation developed in this thesis is based on a discrete element method to track the individual particle and sphere trajectories. Based on a potential based approach for the particle interactions deployed in molecular dynamics, the behavior of the particles can be controlled effectively. The simulated volume is using reflecting boundaries and encloses the hollow sphere. In this work, a highly flexible memory structure was used with a linked cell approach to cope with the highly flexible mass of particles. This allows for a linear complexity of the method in regard to the particle number by reducing the computational overhead of the interaction computation. Multiple numerical experiments show the great effect the particles have on the damping behavior of the system.

Monitoring in Franchise-Netzwerken: Eine ökonomische Analyse - Breuer, Robin

Informationsasymmetrien auf dem Spendenmarkt und Möglichkeiten ihrer Reduktion: Eine Prinzipal-Agenten-Perspektive von Online Spenden - Amedick, Michaela

Pairwise versus Pointwise Ranking: A Case Study - Melnikov, Vitalik; Hüllermeier, Eyke; Kaimann, Daniel; Frick, Bernd; Gupta, Pritha (Schedae Informaticae)

Multiobjective Optimal Control Methods for the Development of an Intelligent Cruise Control - Dellnitz, Michael; Eckstein, Julian; Flaßkamp, Kathrin; Friedel, Patrick; Horenkamp, Christian; Köhler, Ulrich; Ober-Blöbaum, Sina; Peitz, Sebastian; Tiemeyer, Sebastian (Progress in Industrial Mathematics at ECMI)

Second harmonic generation spectroscopy on hybrid plasmonic/dielectric nanoantennas - Linnenbank, Heiko; Grynko, Yevgen; Förstner, Jens; Linden, Stefan (Light: Science & Applications)
Keywords: tet_topic_opticalantenna; tet_topic_shg

Oblique incidence of semi-guided waves on step-like folds in planar dielectric slabs: Lossless vertical interconnects in 3D integrated photonic circuits - Hildebrandt, Andre; Alhaddad, Samer; Hammer, Manfred; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XX)
Keywords: tet_topic_waveguide

Bildungsarbeit in Wirtschaft und Betrieb - Harteis, Christian; Heid, Helmut (Handbuch Bildungsforschung)

A News Editorial Corpus for Mining Argumentation Strategies - Al Khatib, Khalid; Wachsmuth, Henning; Kiesel, Johannes; Hagen, Matthias; Stein, Benno (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics: Technical Papers)

Silicon oxynitride microdisk resonators for integrated waveguide coupling - Hett, Thomas; Frers, Torsten; Widhalm, Alex; Berth, Gerhard; Hilleringmann, Ulrich; Zrenner, Artur (Smart Systems Integration 2016 - International Conference and Exhibition on Integration Issues of Miniaturized Systems, SSI 2016)

Cross-Domain Mining of Argumentative Text through Distant Supervision - Al-Khatib, Khalid; Wachsmuth, Henning; Hagen, Matthias; Köhler, Jonas; Stein, Benno (Proceedings of the 2016 Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies)

A News Editorial Corpus for Mining Argumentation Strategies - Al Khatib, Khalid; Wachsmuth, Henning; Kiesel, Johannes; Hagen, Matthias; Stein, Benno (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics: Technical Papers)

Using Argument Mining to Assess the Argumentation Quality of Essays - Wachsmuth, Henning; Al Khatib, Khalid; Stein, Benno (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics: Technical Papers)

Light scattering by ice crystals of cirrus clouds: From exact numerical methods to physical-optics approximation - Konoshonkin, Alexander; Borovoi, Anatoli; Kustova, Natalia; Okamoto, Hajime; Ishimoto, Hiroshi; Grynko, Yevgen; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
The problem of light scattering by ice crystals of cirrus clouds is considered in the case of a hexagonal ice plate with different distributions over crystal orientations. The physical-optics approximation based on (E, M)-diffraction theory is compared with two exact numerical methods: the finite difference time domain (FDTD) and the discontinuous Galerkin time domain (DGTD) in order to estimate its accuracy and limits of applicability. It is shown that the accuracy of the physical-optics approximation is estimated as 95% for the averaged backscattering Mueller matrix for particles with size parameter more than 120. Furthermore, the simple expression that allows one to estimate the minimal number of particle orientations required for appropriate spatial averaging has been derived.
Keywords: tet_topic_scattering

Comparison between the physical-optics approximation and exact methods solving the problem of light scattering by ice crystals of cirrus clouds - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.; Okamoto, H.; Sato, K.; Ishimoto, H.; Grynko, Yevgen; Förstner, Jens (22nd International Symposium on Atmospheric and Ocean Optics: Atmospheric Physics)
In the problem of light scattering by ice crystals of cirrus clouds, two exact methods (FDTD – finite difference time domain and DGTD – discontinuous Galerkin time domain) and the physical-optics approximation are used for numerical calculations of the Mueller matrix in the case of ice hexagonal plates and columns. It is shown that for the crystals larger than 10 μm at the wavelength of 0.532 μm the exact methods and physical-optics approximation closely agreed within three diffraction fringes about the centers of the diffraction patterns. As a result, in the case of random orientation of these crystals, the physical-optics approximation provides accuracy 95% for the averaged Mueller matrix.
Keywords: tet_topic_scattering

Phase sensitive properties and coherent manipulation of a photonic crystal microcavity - Quiring, Wadim; Jonas, Björn; Förstner, Jens; Rai, Ashish K.; Reuter, Dirk; Wieck, Andreas D.; Zrenner, Artur (Optics Express)
We present phase sensitive cavity field measurements on photonic crystal microcavities. The experiments have been performed as autocorrelation measurements with ps double pulse laser excitation for resonant and detuned conditions. Measured E-field autocorrelation functions reveal a very strong detuning dependence of the phase shift between laser and cavity field and of the autocorrelation amplitude of the cavity field. The fully resolved phase information allows for a precise frequency discrimination and hence for a precise measurement of the detuning between laser and cavity. The behavior of the autocorrelation amplitude and phase and their detuning dependence can be fully described by an analytic model. Furthermore, coherent control of the cavity field is demonstrated by tailored laser excitation with phase and amplitude controlled pulses. The experimental proof and verification of the above described phenomena became possible by an electric detection scheme, which employs planar photonic crystal microcavity photo diodes with metallic Schottky contacts in the defect region of the resonator. The applied photo current detection was shown to work also efficiently at room temperature, which make electrically contacted microcavities attractive for real world applications.
Keywords: tet_topic_phc

Light scattering by irregular particles much larger than the wavelength with wavelength-scale surface roughness - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optics Letters)
We simulate light scattering by random irregular particles that have dimensions much larger than the wavelength of incident light at the size parameter of 𝑋=200 using the discontinuous Galerkin time domain method. A comparison of the DGTD solution for smoothly faceted particles with that obtained with a geometric optics model shows good agreement for the scattering angle curves of intensity and polarization. If a wavelength-scale surface roughness is introduced, diffuse scattering at rough interface results in smooth and featureless curves for all scattering matrix elements which is consistent with the laboratory measurements of real samples.
Keywords: tet_topic_scattering

Light scattering by ice crystals of cirrus clouds: comparison of the physical optics methods - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.; Grynko, Yevgen; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
The physical optics approximations are derived from the Maxwell equations. The scattered field equations by Kirchhoff, Stratton-Chu, Kottler and Franz are compared and discussed. It is shown that in the case of faceted particles, these equations reduce to a sum of the diffraction integrals, where every diffraction integral is associated with one plane–parallel optical beam leaving a particle facet. In the far zone, these diffraction integrals correspond to the Fraunhofer diffraction patterns. The paper discusses the E-, M- and (E, M)-diffraction theories as applied to ice crystals of cirrus clouds. The comparison to the exact solution obtained by the discontinuous Galerkin time domain method shows that the Kirchhoff diffraction theory is preferable.
Keywords: tet_topic_scattering

Pipelines Für Effiziente und Robuste Ad-hoc Textanalyse - Wachsmuth, Henning (Ausgezeichnete Informatikdissertationen 2015)

Discrete plasmonic solitons in graphene-coated nanowire arrays - Kou, Yao; Förstner, Jens (Optics Express)
e study the discrete soliton formation in one- and two- dimensional arrays of nanowires coated with graphene monolayers. Highly confined solitons, including the fundamental and the higher-order modes, are found to be supported by the proposed structure with a low level of power flow. Numerical analysis reveals that, by tuning the input intensity and Fermi energy, the beam diffraction, soliton dimension and propagation loss can be fully controlled in a broad range, indicating potential values of the graphene-based solitons in nonlinear/active nanophotonic systems.
Keywords: tet_topic_plasmonics; tet_topic_polariton

The role of electromagnetic interactions in second harmonic generation from plasmonic metamaterials - Alberti, Julian; Linnenbank, Heiko; Linden, Stefan; Grynko, Yevgen; Förstner, Jens (Applied Physics B)
We report on second harmonic generation spectroscopy on a series of rectangular arrays of split-ring resonators. Within the sample series, the lattice constants are varied, but the area of the unit cell is kept ﬁxed. The SHG signal intensity of the different arrays upon resonant excitation of the fundamental plasmonic mode strongly depends on the respective arrangement of the split-ring resonators. This ﬁnding can be explained by variations of the electromagnetic interactions between the split-ring resonators in the different arrays. The experimental results are in agreement with numerical calculations based on the discontinuous Galerkin time-domain method. (PDF) The role of electromagnetic interactions.... Available from: https://www.researchgate.net/publication/297612326_The_role_of_electromagnetic_interactions_in_second_harmonic_generation_from_plasmonic_metamaterials [accessed Aug 13 2018].
Keywords: tet_topic_shg; tet_topic_meta

Searchable Encryption - Weis, Eduard

Vertiefende Analysen zu ICILS 2013 – Befunde und mögliche Entwicklungsperspektiven - Eickelmann, Birgit; Gerick, Julia; Drossel, Kerstin; Bos, Wilfried (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Singular Curve Point Decompression Attack - Blömer, Johannes; Günther, Peter (2015 Workshop on Fault Diagnosis and Tolerance in Cryptography (FDTC))

Implementing Cryptographic Pairings on Accumulator Based Smart Card Architectures - Günther, Peter; Krummel, Volker (Mathematical Aspects of Computer and Information Sciences)

Theoretical Analysis of the k-Means Algorithm – A Survey - Blömer, Johannes; Lammersen, Christiane; Schmidt, Melanie; Sohler, Christian (Algorithm Engineering)

Hard-Clustering with Gaussian Mixture Models - Blömer, Johannes; Brauer, Sascha; Bujna, Kathrin

Adaptive Seeding for Gaussian Mixture Models - Blömer, Johannes; Bujna, Kathrin (Advances in Knowledge Discovery and Data Mining)

Effizienz und Sicherheit paarungsbasierter Kryptographie - Blömer, Johannes; Günther, Peter

On Non-Cooperative Foundation and Implementation of the Nash Solution in Subgame Perfect Equilibrium via Rubinstein's Game - Duman, Papatya; Trockel, Walter (Journal of Mechanism and Institution Design)

Tightly secure signatures and public-key encryption - Hofheinz, Dennis; Jager, Tibor (Des. Codes Cryptography)

Selective opening security of practical public-key encryption schemes - Heuer, Felix; Jager, Tibor; Schäge, Sven; Kiltz, Eike (IET Information Security)

Black-Box Accumulation: Collecting Incentives in a Privacy-Preserving Way - Jager, Tibor; Rupp, Andy (PoPETs)

How to Generate and Use Universal Samplers - Hofheinz, Dennis; Jager, Tibor; Khurana, Dakshita; Sahai, Amit; Waters, Brent; Zhandry, Mark (Advances in Cryptology - ASIACRYPT 2016 - 22nd International Conference on the Theory and Application of Cryptology and Information Security, Hanoi, Vietnam, December 4-8, 2016, Proceedings, Part II)

Breaking PPTP VPNs via RADIUS Encryption - Horst, Matthias; Grothe, Martin; Jager, Tibor; Schwenk, Jörg (Cryptology and Network Security - 15th International Conference, CANS 2016, Milan, Italy, November 14-16, 2016, Proceedings)

On the Impossibility of Tight Cryptographic Reductions - Bader, Christoph; Jager, Tibor; Li, Yong; Schäge, Sven (Advances in Cryptology - EUROCRYPT 2016 - 35th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Vienna, Austria, May 8-12, 2016, Proceedings, Part II)

Public-Key Encryption with Simulation-Based Selective-Opening Security and Compact Ciphertexts - Hofheinz, Dennis; Jager, Tibor; Rupp, Andy (Theory of Cryptography - 14th International Conference, TCC 2016-B, Beijing, China, October 31 - November 3, 2016, Proceedings, Part II)

Verifiable Random Functions from Standard Assumptions - Hofheinz, Dennis; Jager, Tibor (Theory of Cryptography - 13th International Conference, TCC 2016-A, Tel Aviv, Israel, January 10-13, 2016, Proceedings, Part I)

Verification of AUTOSAR Software Architectures with Timed Automata - Beringer, Steffen; Wehrheim, Heike (Critical Systems: Formal Methods and Automated Verification - Joint 21st International Workshop on Formal Methods for Industrial Critical Systems and 16th International Workshop on Automated Verification of Critical Systems, FMICS-AVoCS 2016, Pisa, Italy, September 26-28, 2016, Proceedings)

Verification of Concurrent Programs on Weak Memory Models - Travkin, Oleg; Wehrheim, Heike (Theoretical Aspects of Computing - ICTAC 2016 - 13th International Colloquium, Taipei, Taiwan, ROC, October 24-31, 2016, Proceedings)